2012
DOI: 10.5863/1551-6776-17.2.159
|View full text |Cite
|
Sign up to set email alerts
|

Inappropriate Vancomycin Therapeutic Drug Monitoring in Hospitalized Pediatric Patients Increases Pediatric Trauma and Hospital Costs

Abstract: OBJECTIVES The objective of this study was to measure the appropriateness of vancomycin monitoring in a pediatric tertiary care center and to evaluate the effectiveness of two interventions, autonomous pharmacy therapeutic drug monitoring and health care provider education, in reducing avoidable pediatric patient trauma and hospital cost. METHODS A retrospective chart review evaluating vancomycin therapeutic drug monitoring (TDM) in pediatric inpatients was performed before and after the introduction of an aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 19 publications
1
12
0
1
Order By: Relevance
“…Our data showed that voriconazole therapeutic drug monitoring would benefit from a multidisciplinary approach, in which the measured trough concentration is viewed in relation to the clinical context. Education alone will likely not be sufficient, because the effect of education on health care professionals is limited 21 and wanes with time, 21,22 especially in teaching hospitals because of frequent changes in staff. A more active role of the pharmacist improved vancomycin therapeutic drug monitoring in hospitalized pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…Our data showed that voriconazole therapeutic drug monitoring would benefit from a multidisciplinary approach, in which the measured trough concentration is viewed in relation to the clinical context. Education alone will likely not be sufficient, because the effect of education on health care professionals is limited 21 and wanes with time, 21,22 especially in teaching hospitals because of frequent changes in staff. A more active role of the pharmacist improved vancomycin therapeutic drug monitoring in hospitalized pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…18,[24][25][26][27][28][29][30][31] Incorrectly drawn anti-Xa levels have several important clinical implications. First, clinicians may be unaware that these are drawn inappropriately and interpret these levels as is.…”
Section: Discussionmentioning
confidence: 99%
“…18,[24][25][26][27][28][29][30][31] To date, there are no studies that primarily identify and describe the practicability of enoxaparin TDM in the literature. Herein, we describe the effectiveness and accuracy of anti-Xa monitoring for patients receiving treatment doses of enoxaparin in the acute care, hospital setting.…”
mentioning
confidence: 99%
“…Because of the significant burden of MRSA infection in hospitals and the community, it is important to use vancomycin appropriately to ensure optimal drug exposure. Though some authors question the usefulness of therapeutic drug monitoring (TDM) of vancomycin and warn of unnecessary hospital costs, appropriate TDM is acknowledged as the most powerful method of adjusting vancomycin use in MRSA bacteremia (2). Studies of the pharmacokinetics and pharmacodynamics (PK/PD) of vancomycin have advocated that a ratio of the area under the curve to the minimum inhibitory concentration (AUC/MIC) of ≥ 400 is optimal for achieving clinical effectiveness in adults (3).…”
Section: Introductionmentioning
confidence: 99%